A review on tools of risk mitigation for information technology management - Anthony Jnr, Bokolo; Che Pa, Noraini (Asian Research Publication Network, 2015)
Information technology (IT) industries are facing operational. Technical and strategic risks that make IT practitioners miss their planned schedule, time and quality. Hence, there is the need to effectively and efficiently mitigate such risks if staffs want to avoid the above problems. Many studies have been accompanied for viewing the issues from different aspects. However, available IT risk mitigation tools present many weaknesses and above all, they are few. 13 studies related to the risk management and mitigation in IT has been reviewed. The studies have been reviewed based on the review method which is called Systematic Literature Review (SLR). Based on this approach, all previous studies related to this title have been studied systematically. Thus this paper aims to do review existing risk tool from 2000 until 2015. Also, this paper presents the results of the systematic reviews on the number of tools in IT risk mitigation. The findings of this review indicate that existing tools for risk mitigation are not completely effective and efficient in mitigating risk that occurs in IT management. This review identifies existing risk mitigation prototypes tools purpose, functionalities, architecture and limitations. The findings of this review also discuss the purpose, functionalities, architecture, limitations of the existing risk mitigation tool in IT Management.